PERAN PERANTAU TERHDAP PEMBANGUNAN NAGARI (Studi Kasus: Jorong Galogandang Nagari III Koto Kec. Rambatan Kab. Tanah Datar) - Emita, Vivi; Zusmelia, Zusmelia; Marleni, Marleni (Pendidikan Sosiologi, 2013)
Travel is a traditional Minangkabau society. This is the case with Galogandang community, other than wander into a tradition of economic and environmental conditions as well as the driving force for the community Galogandang to wander. Lifestyle factors livelihood homogeneous and less adequate fulfillment living day to day is 70% Galogandang community in the region. Based on the conclusion that there are three purposes of research problems, namely: the first settler on the role of design in the development Galogandang region, second the impact of travel on the social and economic life of society Galogandang. This study used a qualitative approach with the case study method of data collection techniques informant interviews to the nomads in the scope of the community and the individual. Through the case study method to guide rational choice theory researchers conducted interviews with 24 informants for the purpose of understanding the phenomena - phenomena taken from research subjects, namely the role of migrants to development Nagari. From the results of this study concluded, the first role that immigrants have a large participation in the development of physical Galogandang, both migrated to the impact of socio-economic life of the community Galogandang in terms of physical and non-physical.